Susceptibility of a number of bivalve species to the protozoan parasite Bonamia ostreae and their ability to act as vectors for this parasite - Culloty, Sarah C.; Novoa, Beatriz; Pernas, María; Longshaw, Matt; Mulcahy, M. F.; Feist, Stephen W.; Figueras Huerta, Antonio (Diseases of Aquatic Organisms, 1999)
8 pages, 1 figure, 7 tables The protozoan parasite Bonamia ostreae (Pichot et al., 1980) is a serious pathogen of the native European flat oyster Ostrea edulis. Field and laboratory based experiments were carried out in Ireland and Spain to investigate the susceptibility to this protozoan of the Pacific oyster Crassostrea gigas, the mussels Mytilus edulis and Mytilus galloprovincialis, the European native clam Ruditapes decussatus and the Manila clam Ruditapes philippinarum. Their ability to act as vectors or intermediate hosts was also investigated. The study corroborated previous findings that demonstrated that flat oysters can be successfully infected both naturally in the field and experimentally in the laboratory, and the pathogen can be transmitted directly between flat oysters in the laboratory. However, the other bivalves tested could not be infected with the parasite either naturally or experimentally, and these bivalves did not appear to act as vectors or intermediate hosts for the parasite. These results have implications for movements of bivalves between areas within the European Union This work was supported by European Union FAIR contract 94C 85/13 Peer reviewed